A Contrastive Analysis Of Consonant Sounds In English And Indonesian “Anti-Hero” Song - Josua Menanti Wind Lumban Tungkup; Mika Dwi Paskaria Ambarita; Desmantha Purba; Anita Sitanggang (CV Putra Publisher, 2023)
The phonetic systems of English and Indonesian are compared and contrasted in the lyrics of the song